2020
DOI: 10.1080/13625187.2020.1736547
|View full text |Cite
|
Sign up to set email alerts
|

Insertion experience of women and health care professionals in the Kyleena® Satisfaction Study

Abstract: Purpose: The Kyleena V R Satisfaction Study (KYSS) is a prospective, observational study conducted to assess satisfaction with LNG-IUS 12 (Kyleena V R) in clinical practice and aims to provide adequate information for counselling women on what to expect regarding insertion and satisfaction. Materials and methods: Women deciding to use LNG-IUS 12 during routine counselling were informed of the study and provided informed consent. A baseline analysis was conducted to evaluate demographics, ease of insertion asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…In total, 100 women (8.9%) either had the device removed or expelled the device before 12 months of use. In the interim KYSS analysis, we reported that 24 women (2.2% of the 1101 participants included in the interim study population) had the device removed within 3 months of use [20]. Based on this and the discontinuation curves depicted in Figures 6 and 7, there does not appear to be any specific timepoint associated with greater discontinuation of LNG-IUS 12. .…”
Section: Continuation and Adverse Events With Lng-ius 12mentioning
confidence: 90%
See 3 more Smart Citations
“…In total, 100 women (8.9%) either had the device removed or expelled the device before 12 months of use. In the interim KYSS analysis, we reported that 24 women (2.2% of the 1101 participants included in the interim study population) had the device removed within 3 months of use [20]. Based on this and the discontinuation curves depicted in Figures 6 and 7, there does not appear to be any specific timepoint associated with greater discontinuation of LNG-IUS 12. .…”
Section: Continuation and Adverse Events With Lng-ius 12mentioning
confidence: 90%
“…Approval from the independent ethics committee/institutional review board (see details in Supplementary Table 1) was obtained for all participating centres. The methodology of this study has been described in detail in the previously published interim analysis, which was conducted after the last woman completed her initial visit at first attempt of LNG-IUS 12 insertion [20]. It should be noted that due to a delay in participant recruitment due to protocols for study acceptance, Mexico completed enrolment after the other countries and was thus not included in the interim analysis.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, over 922 million women of reproductive age rely on some form of contraception [6]. A woman's choice of contraceptive method can depend on a variety of factors, including ease and convenience of use, perceived efficacy, associated costs, and expectations of bleeding pattern [7,8]. Many contraceptive methods, such as oral contraceptive pills, implants, levonorgestrel-releasing intrauterine systems (LNG-IUSs), and copper intrauterine devices are associated with alterations in menstrual bleeding patterns [9][10][11], and some women cite the potential for unfavorable bleeding patterns (such as frequent or prolonged bleeding) or a fear of menstrual irregularity as key reasons for not choosing particular methods [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%